Acoustic microscopy - Briggs, Andrew (Monographs on the physics and chemistry of materials., 2010)
For many years 'Acoustic Microscopy' has been the definitive book on the subject. A key development since it was first published has been the development of ultrasonic force microscopy. This edition has a major new chapter on this technique and its applications.